Experimental investigation of carbon fibre reinforced composites infused with Resin X manufactured using different processes - Ang, Zi Keng (2016)
Currently, in the processing of composite materials using resins, it is more common to use thermosetting resins as the matrix to form composite products because thermosetting resins require lower processing temperature and are less viscous. This causes the resin to easily impregnate into the reinforcement fibre sheets. Thermoplastic resins are less common because they require higher processing temperature and pressure for the resin to impregnate the reinforcing fibre. Furthermore, the composite must be cooled after, which causes the manufacturing process to be comparatively more complex and expensive. A new thermoplastic resin, X, has better processing properties comparable to those of thermosets. Infusing a carbon fibre sheet with Resin X will result in a composite that exhibits the post-processability of thermoplastic properties and yet still share the ease of wetting of the reinforcing fibre just like a thermoset. This project investigates whether composite part products that are infused by Resin X are able to retain its mechanical properties when recycled via thermoforming, in order to determine if it is recyclable through thermoforming. The results showed that the a V shaped part product that was manufactured using the thermoforming process did not perform as well in the load displacement test as a V shaped part product that was infused directly into the V shaped mold. The main cause of the reduction in mechanical strength was due to interlaminar debonding, laminate buckling and delamination during the thermoforming process. However, it was observed that a change in the fibre orientation could significantly increase the mechanical strength of the thermoformed specimens. The results showed that fibre orientation played a significant role in determining the amount of load that the thermoformed part products could withstand. Therefore, the recyclability of products manufactured using Resin X through thermoforming is limited and highly dependent on its fibre orientation.